1997
DOI: 10.1029/97jd00401
|View full text |Cite
|
Sign up to set email alerts
|

The long‐wavelength photochemistry of carbon disulfide

Abstract: Abstract. The photochemistry of carbon disulfide was examined over a concentration range that pertains to tropospheric conditions. At low mixing ratios (67.79, 282.4, and 485.4 parts per billion by volume (ppbv)) in air, photochemical oxidation is very slow and carbonyl sulfide (OCS) product was not observed. Upper limits were established for the quantum yield based on a practical OCS quantification limit of 10 ppbv (•OC8 < 0.0022, 0.00079, and 0.00045, respectively). Solar photolysis at a mixing ratio of 282.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…More recently a CS 2 lifetime 12 days has been suggested (Colman and Trogler 1997), which is in reasonable agreement given the variability of atmospheric OH concentrations. CS 2 can be oxidized in soils (e.g.…”
Section: Cssupporting
confidence: 55%
“…More recently a CS 2 lifetime 12 days has been suggested (Colman and Trogler 1997), which is in reasonable agreement given the variability of atmospheric OH concentrations. CS 2 can be oxidized in soils (e.g.…”
Section: Cssupporting
confidence: 55%
“…Carbon disulfide is an important component of gaseous nebulae, which includes the presolar nebula and primitive planetary atmospheres. It is also a trace atmospheric component with biogenic and anthropogenic sources. At higher concentrations (>10 ppm) carbon disulfide photopolymerizes to yield [CS 2 ] x when irradiated at 313 nm. , Irradiation at shorter wavelengths (λ < 240 nm) causes C−S bond dissociation and yields a complex product mixture . The [CS 2 ] x produced by 313 nm irradiation shows anomalous mass-independent 33 S, 34 S, and 36 S isotopic fractionations that are also observed in sulfur compounds of some meteorites. Photopolymerization of carbon disulfide may thus be an important primary reaction for carbon speciation in the presolar nebula and possibly serve as an agent in trapping planetary gases.…”
mentioning
confidence: 99%
“…Third, the volume fraction of CS2 molecules must be sufficiently large for collisions between long-lived electronically activated CS2* and CS2 or CS molecules in the ground state, and between CS2* and growing (CS2)x moieties to take place for observable particle growth of the photopolymer (Colman and Trogler, 1997). Colman and Trogler (1997) reported that quantum yields for the formation of C S 2 polymer in N2 at 720 Torr seemed to decrease rapidly below CS2 concentrations of 1 ppmv. It seems reasonable to assume that this was due to deactivation by collisions of CS2* with N2 molecules and collisions of CS2* with the walls of the reaction vessel at low CS2 partial pressures.…”
Section: Discussionmentioning
confidence: 99%
“…(1 996) used radiation at 313 nm. Colman and Trogler (1997) also used the Sun as a source of protons and radiation from an arc lamp in the range 280-480 nm. The main absorption features of CS2 are in the ranges 185-215 nm where photodissociation to CS and S occurs and 280-370 nm where photopolymerization prevails.…”
Section: Introductionmentioning
confidence: 99%